Iranian Classical Ney: Pedagogy and Performance - Nezhad, Arya Bastani (Malaysian Journal of Music, 2014)
The Iranian ney is the chief wind instrument of Iranian classical music. This exploration of the structural and key pedagogical elements of ney playing, such as timbre, tone production, posture, inner hearing and expressive fingering, is undertaken through using an autoethnographical approach. The author’s long experience of learning and teaching the ney and Western classical flute has largely contributed to its formation. This will provide a source for ney players, teachers and teacher educators to gain a better understanding of the commonalities and the differences between the two great traditions, Iranian classical and Western classical styles.